"Exploring Online Shopping in Indonesian Context: Are International students satisfied?" : (A Qualitative Research Approach) - Junejo, Safiullah (Journal of Critical Realism in Socio-Economics (JOCRISE), 2023)
Among international students in Indonesia, shopping activity is one of their favorites outside of study. This is because many promotion periods attract international students purchasing intention, such as Ramdhan, Eid, year-end sales, Independence Day Celebration, etc. This study aimed to analyze International students' perceptions of adopters of online shopping in terms of demographic profile, expectations of online stores, advantages, and problems related to online purchases. Moreover, the reasons for using or avoiding online shopping and the types of preferred online shops were studied. The research provides fascinating insights into online consumer behavior. Qualitative analysis was used to analyze the data. This study has collected sixty questionnaires through zoom interviews and online, deployed to international students who have already made an online purchase. Besides offline purchases, online purchasing also has many interests among international students, especially those who are always connected to the internet and technology in every aspect of life. International students prefer online shopping because of its convenience, lower price, many choices, time-saving, and ease of access anywhere and anytime. Based on their experiences, this study reveals that online shopping is cheaper than offline shopping. Moreover, it is also more efficient for them because they have many classes to attend.